THE FIQH OF THE IMAM AND CONGREGATION POSITION AS DESIGN GUIDELINES IN DESIGNING A VERTICAL MOSQUE - Khamdevi, Muhammar (Journal of Islamic Architecture, 2013)
AbstractIn the books of hadeeth and fiqh, it has been narrated many instructions about the imam and congregation position, especially about the position between the imam and the congregation and about the farthest and highest distance of the last row. Suprisingly, if we look closely, these lead us to the possibility in designing a vertical mosque. That is important to address the problem of urban sprawl, where the buildings would have to be directed vertically to solve urban density and to avoid further loss of urban green space. But, is there any high restriction in the hadeeth and the fiqh? Would it be opposed to other hadeeths about the warning of vying to build a magnificent tall mosque? This paper discussed about the possibility in designing a vertical mosque in terms of islamic fiqh and architecture. The research aimed to create a design guideline for vertical mosque and to correct some misconceptions in designing a mosque. This research used a qualitative method, namely literature review. The outcome of this research is the guidelines in designing a vertical mosque.Keywords: Fiqh, Islamic Architecture, Imam and Congregation, Mosque  AbstrakDalam buku-buku hadits dan fiqh banyak diriwayatkan petunjuk-petunjuk mengenai posisi imam dan jamaah, terutama tentang posisi antara imam dan jamaah dan tentang jarak terjauh dan tertinggi dari baris shaf terakhir. Ternyata jika dicermati, ini membawa kita kepada kemungkinan dalam merancang sebuah masjid vertikal. Hal ini sangat penting untuk menjawab masalah urban sprawl, di mana bangunan harus diarahkan secara vertikal untuk mengatasi kepadatan kota dan menghindari kehilangan lebih lanjut dari ruang terbuka hijau. Tapi, apakah ada pembatasan tingginya pada hadits dan fiqh? Apakah itu akan bertentangan dengan hadits lain mengenai peringatan berlomba membangun masjid mewah dan tinggi? Makalah  ini membahas kemungkinan dalam merancang sebuah masjid vertikal dari segi fiqh islam dan arsitektur. Tujuan penelitian ini adalah untuk membuat pedoman desain untuk masjid vertikal dan memperbaiki beberapa anggapan salah dalam  merancang  masjid.  Penelitian  ini  menggunakan  metode  kualitatif,  yakni  literatur  review.  Hasil penelitian ini adalah berupa pedoman desain dalam merancang sebuah masjid vertikal. Kata Kunci: Fiqh, Arsitektur Islam, Imam dan Jamaah, Masjid